Aspek Hukum Lembaga Paksa Badan Terkait Penahanan terhadap Debitur Pailit - Siregar, Bismar Parlindungan; Ginting, Budiman; Sikumbang, Jusmadi; Ramadhan, M. Citra (Universitas Medan Area, 2019)
The purpose of this study is to look at how regulations regarding forced agency (gijzeling / hostage-taking) based on Articles 209 to 224 HIR and Articles 242 to 258 R.Bg, are things that are contrary to human rights and other related regulations. Normative Juridical Approach, namely research focused on studying the application or rules or norms in positive law. There are 2 (two) data collection methods, namely the library research method and the field research method. The results and discussion through the process of developing regulations that apply to forced agency (gijzeling), at this time, this has been revived with the enactment of the Supreme Court Regulation (PERMA) No. 1 of 2000 concerning Forced Institutions, and has been absorbed by the bankruptcy law itself. The issuance of this regulation created the birth of a situation regarding the regulation of the problem of detention of a debtor in Indonesia, which in general has been regulated in Law No. 8 of 1981 concerning Criminal Procedure Law, it is necessary to have restrictions such as what to implement these two regulations, so that it becomes a differentiator in its enforcement.